Estimulación temprana en niños y niñas de educación inicial con problemas del lenguaje en el centro de desarrollo infantil Querubines en el año lectivo 2020-2021. - Gastiabur Barba, Verónica Patricia (2021)
Early stimulation through playful activities has become a complementary tool that helps the infant in its evolution and also to correct some delays in its development. That is why the research presented has the general objective: To analyze the importance of early stimulation through recreational activities, to improve the language problems presented by girls and boys of initial education II, in the Querubines child development center in the 2020-2021 school year. This work has a mixed approach methodology, field design, supported by a documentary review, the type of descriptive research. A population of 20 children, 4 teachers and 19 parents was studied, using research techniques and instruments such as two Likert scale surveys, a pre - test and post - test observation sheet, and an interview. The instruments were validated by experts and their reliability was extracted using Cronbach's Alpha Coefficient, obtaining a level of 0.803 - High Reliability, and one of 0.964 - Very High Reliability. Among the results, it is concluded that teachers and parents require support to help their children develop language and in children with problems reduce their difficulties, for which an AppWeb is established as a proposal that within educational technology contributes to improve the obstacles that impede the complete and comprehensive development of children with respect to their language, obtaining favorable results in its application.